A China e a Globalização: aspectos de uma estratégia nacional - Pires, Marcos Cordeiro [UNESP] (My University, 2011)
The restructuring of the state productive sector of the central government of China is a phenomenon that has occurred since 1978, and is not yet complete. In a centrally planned economy, China's government introduced a series of economic and social transformations in order to modernize the country's economic structure. The flagship of these reforms was the reintroduction of a market economy, living side by side with a strong state control over key economic variables of the country. In this process, there was a restructuring of ownership of enterprises by means of collectivization, the creation of joint stock companies, establishing joint ventures with foreign companies or privatization. The result of this process was the creation of a set of holding companies that operate in strategic sectors of China's economy such as energy, transport, telecom, capital goods and defense. Within this brief article we will focus on the process of opening up and modernization as the expression of a national project that sought to understand the changes in the international economy and sought to adapt the demographic characteristics of China and productive so you get the best out of globalization.

A reestruturação do setor produtivo estatal do governo central da China é um fenômeno que vem ocorrendo desde 1978, e ainda não se encontra concluído. De uma economia centralmente planificada, o governo da China introduziu uma série de transformações econômicas e sociais com vistas a modernizar a estrutura econômica do país. O carro-chefe dessas reformas foi a reintrodução de uma economia de mercado, convivendo lado a lado com um forte controle do Estado sobre as principais variáveis econômicas do país. Nesse processo, ocorreu a reestruturação da propriedade das empresas por meio da coletivização, criação de sociedades por ações, estabelecimento de joint ventures com empresas estrangeiras ou a privatização. O resultado deste processo foi a criação de um conjunto de holdings que atuam nos setores estratégicos da economia chinesas, como energia, transportes, telecomunicações, bens de capital e defesa. No âmbito deste breve artigo, focaremos o processo de Abertura e Modernização como a expressão de um projeto nacional que procurou compreender as modificações da economia internacional e buscou adaptar as especificidades demográficas e produtivas da China de tal forma a tirar o melhor proveito do processo de globalização.
Keywords: República Popular da China; globalização; socialismo de mercado; capitalismo